Problematika Ketetapan Majelis Permusyaratan Rakyat Dalam Hierarki Peraturan Perundang-Undangan di Indonesia - Nilman Ghofur (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2020)
Tap MPR is one source of the legal sequences in the laws and regulations hierarchy in Indonesia. Tap MPR  contains the meaning of Majelis Permusyawaratan Rakyat. Tap MPR was originally included in the hierarchy of statutory regulations in 1965. It is interesting because tap MPR  is still used as a source of law in Indonesia even though legally the MPR is no longer authorized to issue decrees. This article aims to delve deeper into the problems arising from the entry and exit of Tap MPR in the laws and regulations hierarchy in Indonesia. This is very important because there will be confusion in law enforcement if the status of tap MPR changes in the source of the statutory system in Indonesia. The method used is literature by reading books and other journal articles that discuss tap MPR. All data are then analyzed with content analysis to narrow the problem and find solutions to existing problems. This article finds several things, namely that tap MPR  problem contains at least 2 sides of the problem. The first is related to the standing of the MPR and the second is the judicial review of tap MPR. This article makes an important contribution that it turns out that this problem can be solved by several legal steps taken by the government. The first is by giving the right standing to tap MPR and the second is the interpretation of the laws and regulations relating to the judicial review of Tap MPR.